Ecdysteroids from leaves of Vitex trifolia. Issue 2 (4th May 2018) - Thoa, Nguyen Thi Kim; Ban, Ninh Khac; Trang, Do Thi; Linh, Tran My; Giang, Vu Huong; Nhiem, Nguyen Xuan; Van Kiem, Phan
Abstract: Four known ecdysteroids, ecdysone (1 ), 20‐hydroxyecdysone (2 ), 20‐hydroxyecdysone 2, 3‐monoacetonide (3 ), and turkesterone (4 ) were isolated from leaves of Vitex trifolia . The structure of these compounds was elucidated by means of 1D‐ and 2D‐NMR spectra and was compared with those reported in literature. Compound3 was reported from Vitex genus for the first time; compounds1, 2, and4 from V. trifolia for the first time.